Business Process Improvement using Process Mining Techniques. - Zineb LAMGHARI (Faculté des Sciences de Rabat, 2021)
Nowadays, many business process improvement methodologies have been developed and implemented in organisations. These methodologies allow overcoming business improvement challenges in a continuous Business Process Management (BPM) context.
Amélioration des processus métiers par les techniques du process mining
Keywords: Sciences de l’ingénieur; Sciences de l’ingénieur